Crave - Burns, Laura J. (Simon & Schuster BFYR, 2010)
Seventeen-year-old Shay, having suffered from a rare blood disorder her entire life, starts receiving blood transfusion from her step-father who is a physician, and, when she begins to see visions through the eyes of a vampire she decides to investigate, discovering a teenage vampire locked up in the doctor's office who she becomes attached to and set free, only to be kidnapped by the creature who wants revenge.